2021
DOI: 10.1098/rsta.2020.0268
|View full text |Cite
|
Sign up to set email alerts
|

Modern perspectives on near-equilibrium analysis of Turing systems

Abstract: In the nearly seven decades since the publication of Alan Turing’s work on morphogenesis, enormous progress has been made in understanding both the mathematical and biological aspects of his proposed reaction–diffusion theory. Some of these developments were nascent in Turing’s paper, and others have been due to new insights from modern mathematical techniques, advances in numerical simulations and extensive biological experiments. Despite such progress, there are still important gaps between theory and experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 217 publications
(282 reference statements)
0
37
0
Order By: Relevance
“…The system considered here involves a dynamic interplay between the local total density and the metric, which leads to (self-organized) non-uniform growth rates and thereby rich pattern-forming dynamics. Classical Turing models have also been studied for non-uniformly growing lines [71], where, for example, one segment of the line is assumed to grow at a different rate from that of the remaining portion, which can effectively be described as a piecewise uniformly growing line. It was found that this leads to asymmetric pattern formation and peak-splitting of patterns, which can be interpreted as regional patterns in analogy to our work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system considered here involves a dynamic interplay between the local total density and the metric, which leads to (self-organized) non-uniform growth rates and thereby rich pattern-forming dynamics. Classical Turing models have also been studied for non-uniformly growing lines [71], where, for example, one segment of the line is assumed to grow at a different rate from that of the remaining portion, which can effectively be described as a piecewise uniformly growing line. It was found that this leads to asymmetric pattern formation and peak-splitting of patterns, which can be interpreted as regional patterns in analogy to our work.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these classical Turing models have been mainly studied in the quasi-stationary limit [70,71], where one assumes that the pattern-forming dynamics unfolds on a much smaller time scale than domain growth. While such an assumption is reasonable at larger scales, such as in the context of morphogenesis, the time scales of growth and pattern formation are generally not far apart in an intracellular context.…”
Section: Discussionmentioning
confidence: 99%
“…A final, perennial objection to Turing’s reaction-diffusion mechanism is a supposed lack of robustness, that pattern formation depends on the parameters being adjusted within a narrow range. While this is true to a degree of 2-component models, more recent work has shown that having more components, especially if some are non-diffusing ( Marcon et al, 2016 ; Diego et al, 2018 ; Landge et al, 2020 ; Krause et al, 2021 ), and discrete rather than continuous systems ( Leyshon et al, 2021 ), yields models far more robust than previously supposed possible, and there is now a better understanding of how pattern stability is maintained in the non-linear regime ( Subramanian and Murray, 2021 ). The burden of past misconceptions concerning kinetic theories has thus now, in large part, been removed.…”
Section: Flexibility In Pattern Selection: Spots Stripes and In-betweenmentioning
confidence: 99%
“…tern, which is static on a flat plane, was assumed to remain static irrespective of the surface geometry. However, this assumption has not been validated so far [31].…”
mentioning
confidence: 99%